Coinheritance of haemoglobin e trait with alpha thalassaemia among Malay students in national thalassaemia screening programme in Hospital Sultanah Nur Zahirah Kuala Terengganu - Somasundram, Suguna; Abdul Rahman, Alawiyah; Idris, Faridah; Mohd Tohit, Eusni Rahayu (Universiti Putra Malaysia, 2021)
Introduction: Coinheritance of Hb E with alpha thalassaemia may occur. Individuals are asymptomatic for the condition. Further investigations for alpha thalassaemia coinherit with Hb E are dependent upon establishment in lower limit of RBC parameters together with haemoglobin analysis findings. Objectives of the study were to determine coinheritance pattern of Hb E and alpha thalassaemia, significance of RBC parameters and possible cut off level for Hb E for further alpha thalassaemia investigations. Methods: This was a cross sectional study using retrospective data among National Thalassaemia Screening Programme (NTSP) Form Four students. Individuals were classified into three groups (Hb E trait individuals with unknown alpha thalassaemia status, without alpha thalassaemia and with alpha thalassaemia). Descriptive data on gender, mean values of the RBC parameters, Hb A2 and Hb E levels were determined, followed by comparative analysis and ROC curve plotting to determine cut-off value to predict coinheritance of alpha thalassaemia in Hb E traits. Results: The male and female groups are almost equally distributed. Variability in the Hb A2, Hb E levels and RBC parameters values in between groups were noted and some values show significant differences. The cut-off Hb E level to predict the possibility of alpha thalassaemia in Hb E trait is 23.25 %. Conclusion: The proportion of Hb E trait in NTSP of Terengganu state was 17.7 %. Mean RBC parameters between different groups in Hb E trait show variability in values. Hb E ≤23 % can be safely used as a cut-off value to predict coinheritance alpha thalassaemia in Hb E trait.